Pupal colour plasticity in a tropical butterfly, Mycalesis mineus (Nymphalidae: Satyrinae). - Harshad Vijay Mayekar; Ullasa Kodandaramaiah (PLoS ONE)
Lepidopteran insects have provided excellent study systems for understanding adaptive phenotypic plasticity. Although there are a few well-studied examples of adult plasticity among tropical butterflies, our understanding of plasticity of larval and pupal stages is largely restricted to temperate butterflies. The environmental parameters inducing phenotypic plasticity and the selective pressures acting on phenotypes are likely to differ across tropical and temperate climate regimes. We tested the influence of relative humidity (RH), a prominent yet under-appreciated tropical climatic component, along with pupation substrate, larval development time, pupal sex and weight in determining pupal colour in the tropical satyrine butterfly Mycalesis mineus. Pupae of this butterfly are either brown or green or very rarely intermediate. Larvae were reared at high (85%) and low (60%) RH at a constant temperature. Proportions of green and brown pupae were expected to vary across low and high RH and pupation substrates in order to enhance crypsis. Brown pupae were more common at low RH than at high RH, as predicted, and developed faster than green pupae. Pupal colour was correlated with pupation substrate. Choice of pupation substrate differed across RH treatments. It is unclear whether pupal colour influences substrate selection or whether substrate influences pupal colour. Our study underscores the need for further work to understand the basis of pupal plasticity in tropical butterflies.